Influence of the Preoperative Neurological Status on Survival After the Surgical Treatment of Symptomatic Spinal Metastases With Spinal Cord Compression. Issue 23 (December 2015) - Vanek, Petr; Bradac, Ondrej; Trebicky, Ferdinand; Saur, Karel; de Lacy, Patricia; Benes, Vladimir
Abstract : Study Design: Consecutive case-series. Objective: The main purpose of this study was to analyze the relationship between the preoperative neurological status and subsequent survival of patients undergoing surgical treatment for symptomatic spinal metastases. Summary of Background Data: The survival of cancer patients has increased over recent years with improvements in oncologic therapy. As many as 70% of cancer patients develop spinal metastases and ∼10% of all cancer patients are treated for metastatic spinal cord compression. Methods: We retrospectively analyzed 166 patients who underwent surgery for symptomatic spinal metastases in our department between 2005 and 2012. The evaluated factors were age, primary tumor aggressiveness (slow, moderate, rapid growing), spinal location (cervical, thoracic, lumbar, and sacral), operation type (posterior decompression, anterior or posterior instrumented procedure, and radical combined instrumented surgery), preoperative evaluation using the revised Tokuhashi scoring system (<9, 9–11, and 12–15), pre- and postoperative neurological status according to the Frankel score (A-C and D-E), and the site of the main spinal cord compression (anterior, posterior, or combined). Postoperative complication and recurrence rate were also monitored. Results: The mean age of the patients was 62 ± 12 years. The median survival time after surgery was 16.0 months. Preoperative neurological status influenced survival time significantly; the median survival was 5.1 months in Frankel A-C and 28.2 months in Frankel D-E ( P < 0.001). Improvement on the Frankel scale did not influence the survival time ( P = 0.131). When the patients' age was <65 years this related to a significantly longer survival time ( P = 0.046). The Tokuhashi score predicted patient's survival independently ( P < 0.001). The other factors had no statistical significance. Conclusion: The most important factors influencing postoperative survival time of these patients with symptomatic spinal metastases was the preoperative neurological condition and the Tokuhashi scoring system, which together represents a useful tool for planning the extent of surgical treatment.